Measuring World Business Cycles - Allan W. Gregory; Allen C. Head; Jacques Raynauld (Queen's University, Department of Economics, 1994)
Using Kalman filtering and dynamic factor analysis, we decompose fluctuations in real aggregate output, consumption, and investment for the G7 countries into factors that are (i) common across all countries and aggregates, (ii) common across aggregates within a country, and (iii) specific to each data series. In quarterly data for the period 1970-1993, fluctuations in all of the aggregates contain world and country-specific common components which are significant both statistically and economically. Over this period all seven countries experience business cycle episodes primarily attributable to the world cycle and other episodes driven primarily by the country-specific factor. The share of the variance of aggregate output accounted for by the world business cycle in our estimates ranges from 13% for the U.K. to 67% for France. Also, the world common component in growth rates is more strongly serially correlated than is output growth in any of the seven countries.
Keywords: C32; E32; 330; Kalman filter; scoring